2014
DOI: 10.17576/jkukm-2014-26-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physical Properties of Clays Mixed with Silica Sand

Abstract: This study examined the effects of heat treatment on two types of clays mixed with silica sand under laboratory conditions. Soils were subjected to three varied temperatures, i.e. 100, 250

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…FTIR spectrum of H 3 PW 12 O 40 /TEOS catalyst CATALYSTS CRYSTALLINITY BY XRD According to the XRD analysis, the presence of silica compound gave the amorphous state of the catalyst that is produced by sol-gel technique. From XRD pattern in Figure 3, a broader peak displayed at diffraction peak around 28° has represented the Si-O-Si bond as the major component in H 3 PW 12 O 40 /TEOS catalyst while the element of tungsten can be obtained at diffraction angle of 41° and 54° (Firoozi et al 2014). Since the intensity of silica is higher than tungsten in the spectrum, in can be concluded that the sample is mainly in amorphous state.…”
Section: Catalytic Tests Of Glucose Dehydrationmentioning
confidence: 93%
“…FTIR spectrum of H 3 PW 12 O 40 /TEOS catalyst CATALYSTS CRYSTALLINITY BY XRD According to the XRD analysis, the presence of silica compound gave the amorphous state of the catalyst that is produced by sol-gel technique. From XRD pattern in Figure 3, a broader peak displayed at diffraction peak around 28° has represented the Si-O-Si bond as the major component in H 3 PW 12 O 40 /TEOS catalyst while the element of tungsten can be obtained at diffraction angle of 41° and 54° (Firoozi et al 2014). Since the intensity of silica is higher than tungsten in the spectrum, in can be concluded that the sample is mainly in amorphous state.…”
Section: Catalytic Tests Of Glucose Dehydrationmentioning
confidence: 93%
“…Bricks for the pyramids were made from a mixture of lime and clay, and the Romans employed lime to improve the quality of concrete for constructions over 2,000 years ago, which explains the excellent condition of their roadways [8]. The earliest tests with soil stabilization were done in the United States in 1904 [9].…”
Section: Introductionmentioning
confidence: 99%